2020
DOI: 10.1177/1559325820939751
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Berberine Attenuates the Anti-Breast Cancer Activity of Chemotherapeutic Agents via Induction of Autophagy and Antioxidation

Abstract: Berberine (BBR), a major active component of Rhizoma coptidis, is one of the most promising agents for breast cancer adjuvant therapy. It is well accepted that BBR could exhibit remarkable anticancer efficacy with few side effects, and when treated with chemotherapeutic agents in combination, BBR could enhance the chemosensitivity of cancer cells. Our previous study reported that low-dose BBR (LDB) induced hormetic effect and attenuated the anticancer activity of chemotherapeutic agents. However, the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is a crystal yellow-colored isoquinoline alkaloid traditionally used in Chinese and Ayurvedic medicine. Recently, scientists have reported that Berberine possesses broad-spectrum therapeutic potential due to its action against various ailments such as diabetes, hypertension, depression, obesity, inflammation, and cancer [ 9 , 10 , 11 , 12 , 13 ]. Berberine sulfate and hydrochloride have also been considered efficient herbal treatments.…”
Section: Introductionmentioning
confidence: 99%
“…It is a crystal yellow-colored isoquinoline alkaloid traditionally used in Chinese and Ayurvedic medicine. Recently, scientists have reported that Berberine possesses broad-spectrum therapeutic potential due to its action against various ailments such as diabetes, hypertension, depression, obesity, inflammation, and cancer [ 9 , 10 , 11 , 12 , 13 ]. Berberine sulfate and hydrochloride have also been considered efficient herbal treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Similarly, Han et al showed that berberine can enhance the autophagy flux of MCF-7 and MDA-MB-231 cells. [20] However, a study demonstrated that berberine can reduce the number of autophagosomes in doxorubicin (ADR)-resistant MCF-7 cells (MCF-7/ADR) and reverse ADR resistance through PTEN/Akt/ mTOR signaling pathway. [21] Therefore, the role of AMGRBs in BRCA is complex, and more efforts are needed to reveal the potential molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Related to previous research, our study also discovered that BBR exerted an obvious anti‐apoptotic effect. In addition, recent research has demonstrated that a low dose of BBR activates autophagy in macrophages and cancer cells (Han et al, 2020). In the current research, we discovered that BBR strongly increased the lipidated level of LC3 in LPS‐stimulated BEECs in a dose‐dependent manner (Guo, Chen, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%